Implications of Marital Peace in Marriage Counseling: An Ethnographic Case Study - Sai Handari; Achmad Juntika Nurihsan; Ilfiandra Ilfiandra; Yusro Edy Nugroho; Aziza Kavlu (Program Studi BKPI IAIN Salatiga, 2023)
Peace within the household is a critical issue, as the complexities and dynamics of problems can lead to disharmony, which can have adverse physical and psychological effects. To address the need for post-conflict domestic life development, an ethnographic approach is employed. The research focuses on two married couples who have been living together as a child-and-parent couple (father mother, child wife) for 7 and 32 years, respectively. These couples are of Javanese ethnicity. The decision to include couples married for more than 5 years is based on the assumption that they have passed the initial crisis period. The research adopts an ethnographic case study approach, gathering data through interviews and observations. Data were collected through interviews and observations. The findings reveal several important points: (1) Peace is perceived as a blessing within the household, encompassing inner peace, peace with the spouse, in-laws, and the surrounding environment; (2) Factors influencing peace in the household include self-awareness, understanding, and external reflections from the spouse, in-laws, and surrounding environment; and (3) Marital peace has implications for the implementation of marriage counseling, particularly in developing values that prioritize self-optimization when facing marital problems, thereby enabling the realization of potential and independence within the household